Analysis Of Lifestyle Risk Factors On The Occurrence Of Type 2 Diabetes Mellitus: A Systematic Literature Review - Devi Titik Aprila; Asriadi Prihandika Widianto; Budi Widiyanto (Universitas Pahlawan Tuanku Tambusai, 2026)
Type 2 Diabetes Mellitus (T2DM) is becoming increasingly prevalent over the world, posing a serious challenge to public health systems. This rise in prevalence not only affects morbidity and death, but it also imposes a significant economic burden due to treatment expenses, long-term consequences, and reduced productivity. The goal of this study is to discover and assess the most important lifestyle factors in the development of T2DM. Methods: A Systematic Literature Review (SLR) was conducted to consolidate and critically analyze recent epidemiological evidence from 2022 to 2026 regarding lifestyle-related risk factors for Type 2 Diabetes Mellitus. Results: The synthesis reveals that Type 2 Diabetes Mellitus is influenced by a variety of factors, including metabolic and anthropometric factors such as obesity, dietary features such as sugar intake, physical activity, smoking and alcohol consumption, and sleep quality. Conclusion: Obesity, particularly abdominal adiposity, is the most common lifestyle factor contributing to the development of Type 2 Diabetes Mellitus, followed by an unhealthy diet, a lack of physical activity, smoking and alcohol intake, and inadequate sleep quality.